Mengurai Tantangan dan Peluang: Analisis Program Cetar Penting Sebagai Inovasi Pencegahan Stunting di Kecamatan Pariaman Timur - Febriani, Elvina; Yusran, Rahmadani (Journal of Civic Education, 2024)
This study aims to unravel the challenges and opportunities in implementing the Cetar Penting program as an innovation in stunting prevention in East Pariaman District. Using a qualitative approach with a descriptive type, this study involved informants such as the Head of Air Santok Health Center, the person in charge of the Cetar Penting program, village midwives, and Posyandu cadres. Data was collected through interviews and documentation, then tested using the triangulation of sources technique. Data was analyzed through the process of data reduction and conclusion drawing. The results of the study show the existence of supporting factors such as competent human resources and adequate supporting facilities. On the other hand, the lack of public awareness of stunting prevention and weak coordination and communication among relevant actors are the main obstacles. This analysis is expected to provide a deeper insight into efforts to optimize the Cetar Penting program in stunting prevention in East Pariaman District.